How patients view their contribution as partners in the enhancement of patient safety in clinical care - Marie-Pascale Pomey (The Beryl Institute, 2018)
Despite the call from the World Health Organization for more active involvement from patients in the prevention of health care-related risks, there is still insufficient evidence about how patients can be more proactive in the safety of their own care. This study helps understand the perspective of patients as partners regarding their roles, as well as their relatively untapped potential in detecting and limiting adverse events (AEs) for patient safety. 17 patients-as-partners were interviewed on five themes: 1) Behavior of patients/relatives for avoiding AEs; 2) Competencies sought in patients/relatives to play an active role in patient safety; 3) Factors limiting or facilitating the role of patients in the safety of their own care; 4) The Partnership in Care approach as a way of limiting the occurrence of AEs. Patients-as-partners revealed several key behaviours that helped patients avoid AEs: proactivity; communication; trust; vigilance; reporting and flagging; being accompanied by relatives, being accompanied by health professionals. Furthermore, several competencies helped as well: being curious, observant, responsible, able to trust, respectful, and diplomatic. Finally, factors facilitating and limiting patient engagement in safety included personal characteristics, information, interpersonal relations, and organisational aspects. Through the Partnership in Care approach, patients-as-partners develop behaviours and competencies which are yet to be directly applied to improve patient safety. However, obstacles remain: the engagement and official training of patients-as-partners and their appropriate roles in safety, including the identification of AEs; and finally, the redefinition of AEs so as to include the patients’ point of view and experiences.